A Post-Mortem Examination of COVID-19 Pulmonary Pathology in 9 Cases - Alexis Bloom; Austyn Colter; Max Jacobsen; Domnique Battles; Tamara Albertson; George Sandusky (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2020)
A new novel virus called SARS-CoV-2 has expanded into a pandemic in the past several months. The virus is an acute respiratory RNA virus that has symptoms in three clinical groups: asymptomatic, suspicious, and COVID-19 positive. The clinical lab testsused for diagnosis are Nasalpharyngeal swabs, with further testing done with sputum or BAL samples. Serological samples are collected for diagnosis in deceased patients using RT-PCR. The clinical symptoms usually occur 2 to 14 days after exposure and include fever, dry cough, and fatigue. In some cases, symptoms can progress and cause multiple organ failure due to adult respiratory distress syndrome (ARDS). The virus is in the family of coronaviruses and has also been identified in lung tissue using transmission electron microscopy. Gross and microscopic lung pathology was examined in five positive cases and four negative cases by hematoxylin and eosin (H&E) and Masson's Trichrome stains. Of the collected, the age range was 28 to 76. The ethnicities were six Caucasians and three minorities, with a male to female ratio of 7:2. The salient histology features seen in the study were multifocal to diffuse alveolar necrosis, bronchiolar epithelial necrosis, and interstitial mononuclear lymphocytic infiltrates. Other features were perivascular and peribronchiolar lymphoid infiltrates and marked congestion. Scattered fibroplasia was found in the damaged alveoli and the alveolar septae in the more severe cases. These pathologic features are similar to other coronaviruses.